KARAKTERISITIK AUDITOR DAN KECURANGAN LAPORAN KEUANGAN - Tantri, Irga Ayudias; Chariri, Anis (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of auditor industry specialization variables, audit tenure, audit fees and the size of Public Accounting Firms (KAP) on fraudulent financial statements of mining and construction companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The dependent variable in this study was measured using Beneish M-score. The sampling technique used was purposive sampling and was obtained by 59 companies with a total of 295 data. The analysis tool used is logistic regression analysis. The test results showed that independent variables, namely auditor industry specialization, audit tenure, and audit fee do not affect financial statement fraud while the size of KAP affects financial statement fraud.